Fluoride Contamination and Its Optimum Upper Limit in Groundwater from Sukulu Hills, Tororo District, Uganda - Egora, Moses; Birungi, Grace (Scientific African, 2019)
This study was carried out to assess fluoride (F-) concentration and to determine its upper permissible limit in groundwater from Sukulu Hills, a phosphate mining area in Tororo District, Uganda, where groundwater is the main source of drinking water. Water samples were collected from boreholes and protected springs within a three-kilometer radius from the foot of the Hills. The physico-chemical parameters and F- concentration were analyzed using potentiometric methods. The water samples collected had a pH range of 6.0-7.2, electrical conductivity of 148-750 𝜇S/cm, and TDS values of 75-378 mg/L; and these parameters were within the WHO normal range for drinking water. F- concentration in groundwater from boreholes ranged from 0.4 to 3 mg/L, whereas in springs it was from 0.2-2.4 mg/L. High F- levels corresponded with higher TDS values at near-neutral pH. The WHO and Uganda National Bureau of Standards (UNBS) guideline value of 1.5 mg/L F- was exceeded by groundwater from spring S3 and boreholes B3 and B7 (14% of samples) in the study. Given the five-year average weather conditions of Tororo, a modified Galagan equation was applied to calculate the recommended F- of the area, and was found to be 0.4 mg/L. All water sources studied contained average F- levels higher than 0.4 mg/L. These findings imply a possible risk to the local population which depends on this water being exposed to dangers of high F-intake.
Keywords: Fluoride; Groundwater; Sukulu Hills; Tororo; Uganda